2010
DOI: 10.1097/bpb.0b013e32833b6032
|View full text |Cite
|
Sign up to set email alerts
|

An elbow dislocation in a child with missed medial epicondyle fracture and late ulnar nerve palsy

Abstract: Elbow dislocations associated with a medial epicondyle fracture and ulnar nerve palsy are uncommon injuries. We present the case of an 11-year-old girl with an elbow dislocation treated by closed manual reduction. The medial epicondyle fracture was missed initially until she developed an ulnar nerve palsy 2 months later. Intraoperatively we discovered the bony epicondyle piercing the joint capsule and compressing the ulnar nerve. Removal of the bony fragment relieved her symptoms and she returned to normal act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 5 publications
1
12
0
1
Order By: Relevance
“… 4) Nevertheless, late presenting medial epicondyle fractures in association with preoperative ulnar nerve affection is extremely rare. 5 6) The outcome and complications of such an injury pattern have been reported only twice in the English literature. 5 6) The sophisticated developmental anatomy of the pediatric elbow may lead to misinterpretation of radiographs in the phase of acute trauma.…”
mentioning
confidence: 99%
“… 4) Nevertheless, late presenting medial epicondyle fractures in association with preoperative ulnar nerve affection is extremely rare. 5 6) The outcome and complications of such an injury pattern have been reported only twice in the English literature. 5 6) The sophisticated developmental anatomy of the pediatric elbow may lead to misinterpretation of radiographs in the phase of acute trauma.…”
mentioning
confidence: 99%
“…Medial humerus epicondyle fracture is the most common associated injury in complex paediatric elbow dislocation 1 . Intra-articular entrapment of the fracture fragment in the elbow joint occurs in 5-18% of cases 2 but ulnar neuropraxia is rare 1,3,4 . In children, the medial collateral ligament is intact during elbow dislocation contributing to medial humerus epicondyle fracture 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, screw prominence can cause irritation and interference with bone growth, thus implant removal is required at a later stage 2 . Fowles et al recommended anterior ulnar nerve transposition in patients with signs of ulnar nerve compression 3 . However, a study by Chen et al showed that ulnar nerve transposition could increase the risk of ulnar neuritis 5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations